This exquisite loneliness : what loners, outcasts, and the misunderstood can teach us about creativity - Deming, Richard, 1970- (Viking, 2023)
"Imbued with a deep sensitivity for its subjects, and a light touch of memoir that contends with Deming's own struggles with loneliness, THIS EXQUISITE LONELINESS is a singular meditation on the ways that loneliness pervades the human condition, as well as an assertion of the ways in which we might allow our own loneliness to fuel our creative fires. Loneliness is not a feeling to which we readily admit. It is stigmatized, freighted with shame and fear, easy to dismiss as mere emotional neediness. Poet, art critic, and literary theorist Richard Deming contends that to see loneliness this way is to misunderstand it. In THIS EXQUISITE LONELINESS, Deming turns an eye towards that unwelcome feeling, both in his own life and art, and in the lives and the work of six groundbreaking figures. From Melanie Klein's contributions to psychoanalysis and the seminal literature of Zora Neale Hurston to the inventive philosophical writings of Walter Benjamin, and from Walker Evans' photography of urban alienation and Egon Scheile's avant-garde paintings to the ethical underpinnings of Rod Serling's The Twilight Zone, Deming finds a common thread: loneliness served as fuel for an intense creative desire that forged some of the most original and innovative art and writing of the twentieth century. From the "cosmic loneliness" that permeated the life of Zora Neale Hurston to the profound detachment that dogged Rod Serling at the height of his fame, loneliness has long been a complex and slippery subject, as lush and fruitful as it is searingly painful"--